Evaluation of Anionic and Cationic Pulp-Based Flocculants With Diverse Lignin Contents for Application in Effluent Treatment From the Textile Industry: Flocculation Monitoring - Grenda, Kinga; Gamelas, José A. F.; Arnold, Julien; Cayre, Olivier J.; Rasteiro, Maria G. (Frontiers in Chemistry, 2020)
In wastewater treatment, flocculation is a widely used solid/liquid separation technique, typically employing a charged polymer, a polyelectrolyte. Polyelectrolytes features are essential parameters affecting the mechanism of flocculation. Thus, a good understanding of the flocculation kinetics, involved mechanisms and flocs structure is essential in identifying the most adequate treatment conditions. In this study, Eucalyptus bleached pulp and a cellulosic pulp with high lignin content (~4.5 wt%) obtained from Eucalyptus wood waste were used for bio-PELs production. Firstly, a pre-treatment with sodium periodate increased the pulps reactivity. To produce cationic cellulose the oxidation step was followed by the introduction of cationic groups in the cellulose chains, through reaction with Girard reagent T. Applying different molar ratios (0.975 and 3.9) of this reagent to aldehyde groups led to cationic PELs with diverse charge density. To obtain anionic cellulose a sulfonation reaction with sodium metabisulfite was applied to the intermediate dialdehyde cellulose, during 24 h or 72 h, and anionic-PELs with diverse features were obtained. The water soluble, anionic and cationic bio-PELs were characterized and tested as flocculation agents for a textile industry effluent treatment. Initially, jar-tests were used to tune the most effective flocculation procedure (pH, flocculant dosage, etc.). Flocculation using these conditions was then monitored continuously using laser diffraction spectroscopy. Due to the small size of dyes molecules, a dual system with an inorganic complexation agent (bentonite) was essential for effective decolouration of the effluent. Performance was monitored first by turbidity removal evaluation (75%-88% with cationic-PELs, 75%-81% with anionic-PELs) and COD reduction evaluation (79%-81% with cationic-PELs, 63%-77% with anionic-PELs) in the jar tests. Additionally, the evolution of flocs characteristics (structure and size) and the flocculation kinetics, were studied using the LDS technique, applying the different PELs produced and for a range of PEL concentrations. The results obtained through this monitoring procedure allowed to discuss the possible flocculation mechanisms involved in the process. Results obtained with the bio-PELs were compared with those obtained using synthetic PELs, polyacrylamides. The developed bio-PELs can be competitive, eco-friendly flocculation agents for effluents treatment from several industries, when compared to synthetic flocculants with a significant environmental footprint.